Spanish Credit Cooperatives and the Fight against Financial Exclusion - Belmonte Ureña, Luis Jesús; Cortés García, Francisco Joaquín; Molina Moreno, Valentín (Cooperativismo & Desarrollo, 2014)
The aim of this study is to show the importance of Spain’s credit cooperative sector, while also offering a brief view of how families’ savings patterns have evolved. The second section describes the origins of the sector in Spain, emphasizing the relationship between these entities and the primary sector, which is the main source of finance. Later, by describing the features of the credit cooperative sector, as well as offering a profile of its members and its advantages over other forms of banking, some causes are presented for the transformation of these cooperatives, a change they have undergone without losing their focus on members. Accordingly, the third section of this study presents the benefits that credit cooperatives can offer when it comes to financial exclusion, especially when they have become the only social bank in Spain due to the planned demutualization of the savings bank sector.